Proses Promosi Hak Aksesibilitas Bagi Disabilitas Netra melalui Podcast (Studi Pendampingan Produksi Podcast di Mitra Netra Lebak Bulus) - Nusantara, Samiaji Bintang; Asmarantika, Rossalyn Ayu; Indrayuana, Raden Adhitya (Jurnal Pemberdayaan Masyarakat, 2023)
The Podcast Training for the Visually Impaired is a collaborative initiative between Universitas Multimedia Nusantara (UMN) and the Mitra Netra Foundation, aiming to create inclusive opportunities for individuals with visual impairments to engage in podcasting. This program consists of six intensive sessions facilitated by UMN students. It begins with an ideation phase where participants are encouraged to develop podcast concepts based on their personal interests and experiences. Student facilitators guide them in identifying engaging topics. Subsequently, the training progresses to scriptwriting, teaching participants to craft informative and creative scripts with mentorship from student facilitators. The recording phase is crucial, helping participants gain proficiency in sound recording techniques, equipment usage, and addressing potential challenges. Student facilitators play a crucial role in boosting participants' confidence. Finally, the training covers podcast editing, enabling participants to refine their recordings into high-quality podcasts with technical and creative assistance from student facilitators. Beyond technical skills, the Podcast Training for the Visually Impaired promotes social inclusion by providing visually impaired individuals a platform to share their stories through podcasts. This initiative contributes to a more inclusive society and fosters a deeper understanding of diverse perspectives.